Risk Management In The Procurement Process of Upstream Oil Companies Using The House of Risk and Interpretive Structural Modelling: Manajemen Risiko Pada Proses Pengadaan Perusahaan Hulu Minyak Menggunakan Metode House Of Risk Dan Interpretive Structural Modelling - Khabib Fahruddin; Mega Cattleya Prameswari Annissa Islami (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
The procurement process is a crucial component for ensuring smooth and uninterrupted operations in companies. Every activity inherently carries risks, which, while unpredictable, can be mitigated and minimized. This research aims to develop strategic recommendations for effective risk mitigation based on analytical results. This quantitative study identifies key risk prevention strategies and outlines step-by-step mitigation plans. The methods employed are the House of Risk (HOR) and Interpretive Structural Modelling (ISM). Findings from HOR reveal that the most significant risk agent is “sudden user requests requiring immediate completion or breakdown conditions,” with the recommended mitigation being the “tiered training method.” Using ISM, it was determined that “routine coordination with users” is a level 1 risk mitigation strategy. This study concludes that “routine coordination with users” is the most effective mitigation measure, as it influences other mitigations while remaining independent.